Improvisation of solar still: Clean water production - Peter Advent Stephen (2022)
The growth of population globally causes the increase needs of clean water since clean water are needed to be consumed for hydration and for agricultural purposes. Water desalination is a process for producing clean water and the solar water desalination are the method that uses renewable energy source, which is the solar radiation. Improvisation of Solar Still are done throughout this study. Three different Solar Still were designed based on literature reviews. Then all three designs are compared for its feasibility. Several factors are considered and justified before the fabrication of Solar Still. Alongside with the Solar Still, a solar absorber is also implemented, which is made from cotton towel and carbonized sawdust with 55 wt.% of carbon. Then, the Solar Still are tested with seawater sample that is taken from coastal areas of Universiti Malaysia Sabah. Under illumination of the sun for 4 hours, at 10 minutes intervals, readings of evaporation surface temperature and solar radiation were recorded along with the total mass loss of seawater and mass of obtained clean water. The results obtained from this research project shows that the implementation of solar absorber increases the efficiency of Solar Still when compared to bulk seawater setup. Additional features are added in stages which includes reflective surfaces and external thermal insulator and each added features increases the efficiency of Solar Still. The best performing setup, which is the Solar Still setup with solar absorber, reflective surface and external heat insulator shows the efficiency of 60.85%. The quality of produced clean water also examined in this research project and the salinity and pH of produced clean water ranging from 0.01 to 0.03 ppt and 7.41 pH to 7.71 pH respectively and this is within the standards that has been set by the World Health Organization. The fabrication cost for this Solar Still is approximately at RM134.22.